2013
DOI: 10.1158/1078-0432.ccr-12-2754
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Carfilzomib Functions Independently of p53 to Induce Cytotoxicity and an Atypical NF-κB Response in Chronic Lymphocytic Leukemia Cells

Abstract: Purpose The proteasome consists of chymotrypsin-like (CT-L), trypsin-like, and caspase-like subunits that cleave substrates preferentially by amino acid sequence. Proteasomes mediate degradation of regulatory proteins of the p53, Bcl-2 and nuclear factor-κB (NF-κB) families that are aberrantly active in chronic lymphocytic leukemia (CLL). CLL remains an incurable disease, and new treatments are especially needed in the relapsed/refractory setting. We therefore investigated the effects of the proteasome inhibit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 52 publications
4
37
1
Order By: Relevance
“…Previous studies have shown that BM stroma induced resistance to carfilzomib in Waldenstrom Macroglobulinaemia and in CLL (Gupta et al, 2013). Therefore, we tested the effect of BM stroma on the sensitivity of MM cells to carfilzomib, and here we first report that, similar to other haematological malignancies, BM stroma induced drug resistance to carfilzomib.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that BM stroma induced resistance to carfilzomib in Waldenstrom Macroglobulinaemia and in CLL (Gupta et al, 2013). Therefore, we tested the effect of BM stroma on the sensitivity of MM cells to carfilzomib, and here we first report that, similar to other haematological malignancies, BM stroma induced drug resistance to carfilzomib.…”
Section: Discussionmentioning
confidence: 96%
“…These observations are consistent with the report that carfilzomib is less cytotoxic to normal lymphocytes than CLL cells. 9 We next used western blot analysis to assess the effects of carfilzomib treatment on CLL cells isolated before and after ibrutinib treatment from 2 patients, 1 with therapy-related lymphocytosis (CLL-967) and 1 without (CLL-630). Cells from both patients responded in a similar manner to carfilzomib treatment, irrespective of ibrutinib therapy, as indicated by the accumulation of polyubiquitinated proteins, p-IkBa, CHOP, and Noxa ( Figure 1G).…”
mentioning
confidence: 99%
“…(25) CLL cells exposed to increasing doses of carfilzomib showed an accumulation of pIκB and decreased IκB in the cytoplasm, along with nuclear accumulation of NF-κB. Similarly, p53 and select downstream targets of p53 such as p21, NOXA and PUMA were also found to be consistently up-regulated in patient CLL cells(24). …”
Section: Introductionmentioning
confidence: 99%
“…(19, 23) Carfilzomib was also shown to more potently induce apoptosis of CLL cells compared to bortezomib, and unlike bortezomib, was equally effective in media with human versus fetal bovine serum. (24) Furthermore, carfilzomib can induce cell death in bortezomib-resistant cells. (22) One potential mechanism of cell death is through the NF-kB pathway, which is well-established to promote survival signaling in CLL.…”
Section: Introductionmentioning
confidence: 99%